Colonic Adenocarcinomas Harboring NTRK Fusion Genes: A Clinicopathologic and Molecular Genetic Study of 16 Cases and Review of the Literature. (February 2020) - Lasota, Jerzy; Chłopek, Małgorzata; Lamoureux, Jennifer; Christiansen, Jason; Kowalik, Artur; Wasąg, Bartosz; Felisiak-Gołąbek, Anna; Agaimy, Abbas; Biernat, Wojciech; Canzonieri, Vincenzo; Centonze, Giovanni; Chmielik, Ewa; et al.
Abstract : This study was undertaken to determine the frequency, and the clinicopathologic and genetic features, of colon cancers driven by neurotrophic receptor tyrosine kinase ( NTRK ) gene fusions. Of the 7008 tumors screened for NTRK expression using a pan-Trk antibody, 16 (0.23%) had Trk immunoreactivity. ArcherDx assay detected TPM3-NTRK1 (n=9), LMNA-NTRK1 (n=3), TPR-NTRK1 (n=2) and EML4-NTRK3 (n=1) fusion transcripts in 15 cases with sufficient RNA quality. Patients were predominantly women (median age: 63 y). The tumors involved the right (n=12) and left colon unequally and were either stage T3 (n=12) or T4. Local lymph node and distant metastases were seen at presentation in 6 and 1 patients, respectively. Lymphovascular invasion was present in all cases. Histologically, tumors showed moderate to poor (n=11) differentiation with a partly or entirely solid pattern (n=5) and mucinous component (n=10), including 1 case with sheets of signet ring cells. DNA mismatch repair–deficient phenotype was seen in 13 cases. Tumor-infiltrating CD4/CD8 lymphocytes were prominent in 9 cases. Programmed death-ligand 1 positive tumor-infiltrating immune cells and focal tumor cell positivity were seen in the majority of cases. CDX2 expression and loss of CK20 and MUC2 expression were frequent. CK7 was expressed in 5 cases. No mutations in BRAF, RAS, and PIK3CA were identified. However, other genes of the PI3K-AKT/MTOR pathway were mutated. In several cases, components of Wnt/β-catenin ( APC, AMER1, CTNNB1), p53, and TGFβ ( ACVR2A, TGFBR2 ) pathways were mutated. However, no SMAD4 mutations were found. Two tumors harbored FBXW7 tumor suppressor gene mutations. NTRK fusion tumors constitute a distinct but rare subgroup of colorectal carcinomas. Abstract : Supplemental Digital Content is available in the text.